In silico chemical screening identifies epidermal growth factor receptor as a therapeutic target of drug-tolerant CD44v9-positive gastric cancer cells - Mashima, Tetsuo (Br J Cancer, 2019)
BACKGROUND: Tumours consist of heterogeneous cancer cells and are likely to contain drug-tolerant cell subpopulations, causing early relapse. However, treatment strategies to eliminate these cells have not been established. METHODS: We established gastric cancer patient-derived cells (PDCs) to examine the contribution of CD44 splicing variant 9 (CD44v9)-positive cells in gastric cancer drug tolerance. We performed gene expression signature-based in silico screening using JFCR_LinCAGE, our anticancer compound gene expression database and subsequent validation in BALB/c-nu/nu mouse xenograft to identify agents targeting the drug-tolerant cancer cells. RESULTS: CD44v9-positive cancer cells were enriched among residual cancer cells after treatment with SN-38, an active metabolic of irinotecan. CD44v9 protein was responsible for this drug resistance. We identified epidermal growth factor receptor (EGFR) inhibitors as agents that can target CD44v9-positive cell populations in gastric cancer PDCs. CD44v9 promoted cell proliferation, and EGFR inhibition attenuated CD44v9 protein expression through downregulation of the AKT and the ERK signalling pathways, leading to preferential suppression of CD44v9-positive cells. Importantly, EGFR inhibitors significantly reduced the number of residual cancer cells after cytotoxic anticancer drug treatment and enhanced the antitumor effect of irinotecan in vivo. CONCLUSIONS: EGFR inhibitors could be potential agents to eradicate cytotoxic anticancer drug-tolerant gastric cancer cell populations.